Development of mobile app for private tutoring - Ng, Mark Jinn Rong (Nanyang Technological University, 2024)
Many students often feel lost and overwhelmed due to the many assignments, projects and examinations that students have to be constantly preparing for. For many students, searching for avenues for help can be daunting and difficult as some material are not easily or readily found. This project is designed to address the demands of university life by providing students with a user friendly mobile platform. Bringing students taking the same module closer together as they will be able to communicate easily with each other and find material relating to the modules that they are taking with ease. This project will utilise Flutter for cross-platform development such that all students will be able to utilise it.